Impact of increased diagnosis of early HIV infection and immediate antiretroviral treatment initiation on HIV transmission among men who have sex with men in the Netherlands. - Alexandra Teslya; Janneke Cornelia Maria Heijne; Maarten Franciscus Schim van der Loeff; Ard van Sighem; Jacob Aiden Roberts; Maartje Dijkstra; Godelieve J de Bree; Axel Jeremias Schmidt; Kai J Jonas; Mirjam E Kretzschmar; Ganna Rozhnova (PLoS Computational Biology)
The number of new HIV infections among men who have sex with men (MSM) in the Netherlands has been decreasing, but additional efforts are required to bring it further down. This study aims to assess the impact of increased diagnosis of early HIV infection combined with immediate antiretroviral treatment (ART) initiation on reducing HIV transmission among MSM. We developed an agent-based model calibrated to HIV surveillance and sexual behavior data for MSM in the Netherlands in 2017-2022. Starting in 2023, we simulated a 10-year intervention that accelerates HIV diagnosis during the first 3 or 6 months after HIV acquisition across five levels of increased diagnosis rates (2, 4, 8, 16, and 32-fold), followed by immediate ART initiation. The upper limit of the intervention's impact over 10 years is projected to result in the cumulative 298 (95-th QI: 162-451) HIV infections averted. A 32-fold increase in the diagnosis rate within 3 months after HIV acquisition (corresponding to 100% of all new HIV infections diagnosed within 3 months of acquisition) results in 269 (95-th QI: 147-400) infections averted, approaching closely maximum impact. By extending the scope of the intervention to individuals who acquired HIV infection within the previous 6 months, a smaller 8-fold increase in the diagnosis rate (corresponding to 97% of new HIV infections diagnosed within 6 months of acquisition) approaches closely the maximum impact of the intervention by averting 256 (95-th QI: 122-411) HIV infections. Our sensitivity analyses showed that, in an epidemiological context similar to the modern-day the Netherlands, immediate initiation of ART accompanying accelerated diagnosis of individuals with early HIV infection does not significantly affect HIV transmission dynamics. Accelerating early HIV diagnosis through increased awareness, screening, and testing can further reduce transmission among MSM. Meeting this goal necessitates a stakeholder needs assessment.